Guiding Dyslexic Learners: The Crucial Role of Counseling Teachers and Multisensory Learning - Rahmawati Rahmawati; Labiyb Abqariy; Saiful Muktiali; Listian Indriyani Achmad (Aqlamuna: Journal of Educational Studies, 2024)
This study aims to explore the role of school counselors in assisting dyslexic students in overcoming learning difficulties through the use of multisensory methods, focusing on Class 2B at MI Al-Istiqomah. Dyslexia is a specific learning disorder that affects a student's ability to read and write, often leading to frustration and underachievement in the classroom. To address these challenges, school counselors play a pivotal role in offering both psychological support and appropriate instructional strategies. One such strategy is the multisensory method, which engages various senses—such as touch, sight, and hearing—to reinforce learning in a more integrated and accessible way for dyslexic students. This research adopts a qualitative descriptive approach with a case study method. Data were collected through observation, in-depth interviews with school counselors and teachers, and documentation of the learning process. The findings indicate that the application of multisensory techniques—such as tracing letters with fingers, using visual aids, and incorporating audio tools—significantly helps dyslexic students in improving their reading and writing skills. Moreover, the involvement of the counselor boosts students’ motivation and reduces their anxiety, creating a more supportive and engaging learning environment. The study contributes to the understanding of effective intervention strategies for dyslexic learners in primary school settings. It highlights the essential role of school counselors not only as emotional supporters but also as instructional partners who can facilitate inclusive education through innovative, multisensory approaches tailored to individual student needs.